1998
DOI: 10.1080/026404198366777
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between blood lactate and heart rate responses to swim bench exercise and women's competitive water polo

Abstract: The aim of this study was to explore the relationship between physiological responses to dry-land testing and to water polo playing. Eight female water polo players (mean+/-s: age 26.7+/-5.7 years, height 169+/-6 cm, body mass 65.3+/-7.0 kg) participated in two assessments. The first involved a discontinuous incremental arm test to exhaustion on an isokinetic swim bench. Blood lactate was determined from finger-prick blood samples and heart rate was recorded at increasing exercise intensities. The highest (pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
2
6
0
6
Order By: Relevance
“…A similar conclusion was reached in an investigation of female players studied during a single match of the top level league in the Netherlands, although the mean blood lactate values reported were somewhat lower than those reported above: 4.9-5.8 mmol/L (range = 1.5-9.8 mmol/L; Hollander et al, 1994). Similar blood lactate values have been observed during match play in male and female players (Konstantaki et al, 1998;Platanou and Geladas, 2006;Platanou and Nikolopoulos, 2003).…”
Section: Physiological Demands and Fatigue During Competitionsupporting
confidence: 79%
“…A similar conclusion was reached in an investigation of female players studied during a single match of the top level league in the Netherlands, although the mean blood lactate values reported were somewhat lower than those reported above: 4.9-5.8 mmol/L (range = 1.5-9.8 mmol/L; Hollander et al, 1994). Similar blood lactate values have been observed during match play in male and female players (Konstantaki et al, 1998;Platanou and Geladas, 2006;Platanou and Nikolopoulos, 2003).…”
Section: Physiological Demands and Fatigue During Competitionsupporting
confidence: 79%
“…In terms of metabolic responses to exercise, the blood lactate concentration and heart rate at the end of an arms-only test on an isokinetic LBSE were found to be similar to the end of a water polo game. 33 Also, similar values were found during whole-body LBSE and actual swimming when swimmers were compared to non-swimmers for lactate concentration 34 and stroke volume. 35 These findings support the idea of comparable physiological responses between actual swimming and LBSE, and supports the potential to detect the differences in physiological responses to exercise due to performance level, using LBSE.…”
Section: Discussionsupporting
confidence: 65%
“…It also gives information on submaximal stages, such as the ventilatory thresholds, which are relevant to endurance performance [3, 12, 15]. Konstantaki et al [17] showed that submaximal responses, rather than peak dry land bench test responses, were correlated with game HR in female water polo players. Moreover, despite being in a pool, water polo players are frequently in a vertical position (to defend, wait for the ball, shoot, etc.)…”
Section: Discussionmentioning
confidence: 99%